One-pot high-throughput synthesis of N3-substituted 5-arylidene-2-thiohydantoin amides and acids. (3rd August 2022) - Whitely, Chelsi; Li, Yangmei
Graphical abstract: Abstract: A one-pot high-throughput solid-phase method for the synthesis of N 3-substituted 5-arylidene-2-thiohydantoin amide and acid has been developed. A tandem ring-closure and ring-open pathway is proposed as the mechanism of forming the two products.